Feasibility of detecting myocardial infarction in the sheep fetus using late gadolinium enhancement CMR imaging - An Qi Duan; Mitchell C. Lock; Sunthara Rajan Perumal; Jack R. Darby; Jia Yin Soo; Joseph B. Selvanayagam; Christopher K. Macgowan; Mike Seed; Janna L. Morrison (Journal of Cardiovascular Magnetic Resonance, 2017)
Abstract Background Late gadolinium enhancement (LGE) cardiovascular magnetic resonance (CMR) imaging has enabled the accurate assessment of myocardial infarction (MI). However, LGE CMR has not been performed successfully in the fetus, where it could be useful for animal studies of interventions to promote cardiac regeneration. We believe that LGE imaging could allow us to document the presence, extent and effect of MI in utero and would thereby expand our capacity for conducting fetal sheep MI research. We therefore aimed to investigate the feasibility of using LGE to detect MI in sheep fetuses. Methods Six sheep fetuses underwent a thoracotomy and ligation of a left anterior descending (LAD) coronary artery branch; while two fetuses underwent a sham surgery. LGE CMR was performed in a subset of fetuses immediately after the surgery and three days later. Early gadolinium enhancement (EGE) CMR was also performed in a subset of fetuses on both days. Cine imaging of the heart was performed to measure ventricular function. Results The imaging performed immediately after LAD ligation revealed no evidence of infarct on LGE (n=3). Two of four infarcted fetuses (50%) showed hypoenhancement at the infarct site on the EGE images. Three days after the ligation, LGE images revealed a clear, hyper-enhanced infarct zone in four of the five infarcted fetuses (80%). No hyper-enhanced infarct zone was seen on the one sham fetus that underwent LGE CMR. No hypoenhancement could be seen in the EGE images in either the sham (n=1) or the infarcted fetus (n=1). No regional wall motion abnormalities were apparent in two of the five infarcted fetuses. Conclusion LGE CMR detected the MI three days after LAD ligation, but not immediately after. Using available methods, EGE imaging was less useful for detecting deficits in perfusion. Our study provides evidence for the ability of a non-invasive tool to monitor the progression of cardiac repair and damage in fetuses with MI. However, further investigation into the optimal timing of LGE and EGE scans and improvement of the sequences should be pursued with the aim of expanding our capacity to monitor cardiac regeneration after MI in fetal sheep.